Bridging the gap between objective and subjective well-being among first generation immigrants: exploring the role of religion and spirituality - Batuwanthudawa, Samadara; Udayanga, Samitha (Frontiers in Sociology, 2025)
The role of religion and spirituality in fostering resilience among immigrants has been widely acknowledged. However, existing studies often emphasize religious affiliations established within the host country, overlooking the significance of religious practices originating from immigrants’ home countries and their unique influence on the life experiences of immigrants. The present study thus addresses this research gap by investigating how religious affiliations rooted in immigrants’ home country based traditions influence their subjective well-being in a new social context. Using a qualitative approach, we examined the experiences of Sri Lankan immigrants settled in Italy. The thematic analysis identified two key themes. The first theme highlights that, although religious practices may initially appear less significant upon immigration, their importance resurfaces during periods of uncertainty. By providing psychological stability, these practices enhance both objective and subjective dimensions of well-being. The elevated levels of happiness observed among immigrants often reflect strong affiliations with home country based religious institutions and spirituality aligned closely with home country cultural values. The second theme demonstrates that religion functions as a cultural bridge, enabling immigrants to transfer familiar traditions and practices into their new environment. Overall, the process of reconnecting with home country based religious practices and spirituality allows immigrants to navigate the host country effectively, balancing the establishment of objective well-being with the preservation of valued cultural identities, and ultimately enhancing their subjective well-being.